Analytical Model of an Optically Controlled DCFL Inverter Using Normally-off MESFET's - Bandhawakar G.; Jit S.; Pal B.B. (My University, 2025)
An Analytical model of an optically controlled DCFL (Direct Coupled Field Effect Transistor) inverter using normally off MESFET (E-MESFET) has been presented in this paper. An enhancement mode MESFET with a transparent/semi-transparent Schottky gate has been used as the switching transistor and an ungated MESFET has been used as the load of the inverter. The gate across the transistor is illuminated by optical radiation to develop a photovoltage at the Schottky junction which may be used to control it's operation. The transfer characteristics of the inverter with fan out=0 and 1 have been presented under both the dark and illuminated conditions of the MESFET. The result demonstrates better performance under illumination as compared to that under dark condition.